Low level laser therapy versus benzydamin in prevention and treatment of oral mucositis induced by anticancer treatments (clinical and biochemical study) - Helaly Mohamed, Nashwa; Mohammed Kamel , Asem; Edress, Mohamed Fouad; Mahmoud, Azza Shibl Sayed; Gaafar, Ashraf Ibrahim Abd El-Halim (Brazilian Dental Science, 2022)
Objective: In this study, patients undergoing neck and head radiotherapy (RT) with or with no chemotherapywere contrasted to the low-level laser therapy (LLLT) efficacy against benzydamine hydrochloride in treating andpreventing oral mucositis (OM) (CHT). Material and Methods: This study included 90 individuals with neckand head cancer who were undergoing radiotherapy (RT) individually or in mixture with chemotherapy (CHT),varying in age from 18 to 80 years. Three equal groups were randomly formulated: Group, I patients were usingoral care only, Group II patients were using benzydamine hydrochloride mouth rinse, and Group III patientswere medicated by using low-level laser therapy. The National Institute of Cancer-Common Toxicity Criteria(NIC-CTC) and the World Health Organization (WHO) were used to rate the severity of OM, and the pain wasvalidated utilizing a visual analog scale (VAS). The salivary level of tumor necrotic factor-a (TNF- a) was assayed. Results: As per WHO and NIC, the grade of oral mucositis at the end of cancer treatment was less in the LLLTgroup than in the other two groups. The alteration in TNF-a level was not significant. The laser group is moreliable to have less salivary levels of the pro-inflammatory cytokines TNF- a. Conclusion: The incidence of oralmucositis severity has seemed to be reduced due to the prophylactic use of benzydamine hydrochloride and lasertherapy protocols. However, laser therapy was more efficient in controlling the shape and progression of OM.KEYWORDSOral mucositis; Photobiomodulation; Radiation therapy; Chemotherapy; Low-level laser therapy; Benzydamine